New record of Dryinidae from Nicaragua and a descrition of a new species (Hymenoptera: Chrysidoidea) - Olmi, B.
(En, Es)
Ilus., 3 ref.
Keywords: TAXONOMIA; HYMENOPTERA; INSECTA; REGISTRO; ESPECIES NUEVAS; DISTRIBUCION GEOGRAFICA; NICARAGUA; REVISTA NICARAGUENSE DE ENTOMOLOGIA